A Systematic Review and Meta-Analysis of the Role of Sugar-Free Chewing Gum on Plaque Quantity in the Oral Cavity - Nasseripour, Melanie; Newton, Jonathon Timothy; Warburton, Fiona; Awojobi, Oluwatunmise; Di Giorgio, Sonya; Gallagher, Jennifer Elizabeth; Banerjee, Avijit (Frontiers in Oral Health, 2022)
Abstract Background: The aim of this systematic review of published literature was to answer the research question, “What is the difference in the level of plaque quantity, in adults and children who chew sugar-free gum (SFG), compared with those who do not chew SFG, who do not chew gum or who use alternatives such as probiotics or fluoride varnish?” Methods: The systematic review (registered on PROSPERO 2018 (CRD42018094676)) included studies on adults and children with chewing of SFG as the main intervention, where “sugar” referred to monosaccharides and disaccharides. Studies included were in English language and corresponded to primary research between 1946 and 2020. The search conducted spanned all relevant databases using both Medical Subject Headings (MESH) and free text with combinations of “chewing gum”, “sugar-free”, “caries”, “xerostomia”, “periodontal disease”. Results: Eight papers included plaque quantity as part of their outcomes. Meta-analysis showed that SFG significantly reduced plaque quantity (effect size -0.778; 95% CI -1.167 to -0.39). There was a high degree of heterogeneity between studies with I2=86.6%. The correlation between the baseline and the end of study data were assumed to be 0.95 for the control and 0.65 for the SFG group. A sensitivity analysis was conducted with the pre- to post-test correlation set at 0.95 for the SFG group. This gave an effect size of -1.098 (95% CI -1.539 to -0.656) with an I2=89.73%. When looking more specifically looking at xylitol gum, the results of the meta-analysis showed that it significantly reduced plaque quantity (effect size -0.743; 95% CI -1.148 to -0.338). There was a high degree of heterogeneity between studies with I2=86.0%. Conclusion: There is some evidence that chewing sugar-free gum, in particular xylitol SFG, reduces the quantity of plaque in the oral cavity in comparison to non SFG chewing or no chewing controls. Further research with improved design, lengthier timeframes and higher number of participants should be considered.